Short-term Complications, Reoperations, and Radiographic Outcomes of the Infinity Total Ankle Arthroplasty. Issue 3 (14th September 2018) - Saito, Guilherme; Sanders, Austin; de Cesar Netto, Cesar; O'Malley, Martin; Ellis, Scott; Demetracopoulos, Constantine
Category: Ankle Arthritis Introduction/Purpose: With the increasing use of total ankle arthroplasty (TAA), new implants with varied configurations are being developed every year. This study aims to provide the early complications, reoperations and radiographic and clinical outcomes of the Infinity TAA. To date, clinical results of this novel fixed-bearing implant have not been published. Methods: A retrospective analysis of 64 consecutive ankles that underwent a primary Infinity TAA from July 2014 to April 2016 was performed. Patients had an average follow-up of 24.5 (range, 18-39) months. Medical records were reviewed to determine the incidence of complications, reoperations and revisions. Radiographic outcomes included preoperative and postoperative tibiotalar alignment, tibial implant positioning, the presence of periprosthetic radiolucency and cysts, and evidence of subsidence or loosening. Additionally, patient-reported outcomes were analyzed with the Foot and Ankle Outcome Score (FAOS) preoperatively and 1-year postoperatively. Results: Survivorship of the implant was 95.3%. Fourteen ankles (21.8%) presented a total of 17 complications (Table 1). A total of 12 reoperations were necessary in 11 ankles (17.1%). Revision surgery was indicated for 3 ankles (4.7%) due to isolated subsidence of the tibial implant in 2 cases and due to subsidence of both the tibial and talar components in 1 case. Tibiotalar coronal deformity was significantly improved after surgery (P < .0001) and maintained during latest follow-up (P = .81). Periprosthetic radiolucent lines were observed around the tibial component in 20 ankles (31%) and around the talar component in 2 ankles (3.1%). A tibial cyst was observed in 1 ankle (1.5%). Outcome scores were significantly improved for all FAOS components analyzed (P < .0001). Conclusion: Most complications observed in the study were minor and successfully treated with a single reoperation procedure or nonoperatively. Failures and radiographic abnormalities were most commonly related to the tibial implant. Further studies with longer follow-up are needed to evaluate the survivorship of the tibial implant in the long-term.